Management of CBD Stone in Situs lnversus Total is: A Case Report - Khan, Sadia Armin; Ashraf Ali, Abu Ahmed; Salam, Abdus; Hossain, Syeda Samina; Chowdhury, Sharupa; Sarkar, Anusree (Journal of Surgical Sciences, 2019)
Situs inversustotalis is a rare congenital condition present in approximately 0.01% of thepopulation in which the major visceral organs are reversed from their normal position and canpose difficulties in the diagnosis and management of abdominal pathology. Symptomaticcholelithiasis is very common and laparoscopic cholecystectomy is the gold standard treatmentat present. Laparoscopic surgery in a situation of situs inversus is challenging due tothe mirror-image anatomy. Diagnostic pitfalls and technical details of the laparoscopic cholecystectomyare discussed. Journal of Surgical Sciences (2017) Vol. 21 (1) :48-50